Hubungan Efikasi Diri dengan Quarter Life Crisis pada Mahasiswa yang Mengikuti Organisasi di Universitas Negeri Padang - Putra, Revan Revelino; Aulia, Farah (Lembaga Yasin AlSys, 2024)
In facing the quarter life crisis period, students have high self-efficacy so that individuals can face the quarter life crisis period smoothly. Individuals who have self-efficacy will resolve it effectively when facing difficult situations and will focus on resolving it smoothly. BEM is a forum for students to channel their aspirations and also develop their potential so that they have the skills needed in the future. The type of research used is quantitative research with a correlational research design. The sample was taken based on the provisions of the Isaac and Michael table with an error rate of 1% with a total of 269 students from a population of 450 students who took BEM at both faculty and university levels at UNP. The sampling technique used in this research was the Accidental Sampling technique. Based on the results of research on the relationship between self-efficacy and quarter life crisis, it can be concluded that self-efficacy for students taking BEM at UNP is in the medium category with a percentage of 90%, Quarter life crisis for students taking BEM at UNP is in the medium category with a percentage of 85 .9% and self-efficacy and quarter life crisis in students taking BEM at UNP have a correlation of -0.379 with a low relationship. Self-efficacy and quarter life crisis are also negatively related, meaning that the higher self-efficacy, the quarter life crisis will decrease. Conversely, if self-efficacy is low then the quarter life crisis will increase.